In silico screening of FDA-approved drugs for antiviral activity against the influenza virus: a novel approach to the repurposing of existing medications - Hashim, Hayder Obayes; Makki Al-Hindy, Hayder Abdul-Amir; Bakr, Aya Muthana; Hayif, Qabas Amer; Humadi, Yaqeen Taleb (Pharmakeftiki, 2025)
This study investigated the efficacy of FDA-recognized compounds in preventing influenza virus infections, using in silico analysis. By focusing on the structural characteristics of neuraminidase (a key target in antiviral therapy), the study identified 12 critical regions amenable to drug interaction. Among the evaluated compounds, lysine emerged as the most promising candidate, exhibiting an XP GScore of -9.912 and relatively high binding affinity. Molecular docking simulations revealed that lysine engages essential amino acid residues within the neuraminidase active site through hydrogen bonding and salt-bridge formation, thereby supporting its potential to inhibit viral replication. Other compounds, including iohexol and capastat, also demonstrated notably high binding constants. These findings underscore the feasibility of drug repurposing, particularly involving known dietary supplements such as lysine, as a strategic response to emerging antiviral resistance, severe influenza cases, and seasonal outbreaks. The results provide a preliminary experimental framework to guide future studies and support the clinical deployment of these agents against influenza and related infections.